STRATEGI PEDAGANG SAYURAN DI PASAR CIK PUAN KECAMATAN SUKAJADI KOTA PEKANBARU - Indah Sari; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Cik Puan Market is a strategic market located precisely in the District of Sukajadi which is densely populated in Pekanbaru City. Located in the city center, near this market there used to be a terminal so that this market is very famous, because many people pass by. However, this changed after the market caught fire and the transfer of the terminal to Akap. So that traders in the Cik Puan market have considerable economic competition, especially vegetable traders because of the following reasons, namely, the large number of vegetable traders in the Cik Puan market, the many shocked markets that push lower prices, bad weather which makes traders a place to trade vegetables get wet, dirty, even stagnant which worsens. Reducing the interest of visitors to the Cik Puan market. So that the vegetables they sell are unsold and rot. Therefore, a vegetable trader strategy is needed to continue to exist and be able to survive trading in the Cik Puan market and be able to meet the needs of their families. So in this study, it will be seen how obstacles and opportunities for vegetable traders to survive trading vegetables in the Cik Puan market to meet the needs of their families, the strategies are active strategies, passive strategies and network strategies. The research is located in the Cik Puan market, Sukajadi District, Pekanbaru City. Using a qualitative case study method by conducting in-depth observations and interviews with 2 key informants and 5 informants. The results of this study indicate that the strategies carried out by the 5 informants are more likely to use active and passive strategies. But the network strategy is the weakest strategy and the most active one is the active strategy. Keywords: Strategy, Vegetable Traders